2015
DOI: 10.1177/1932202x15615316
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Psychosocial Characteristics of High Achieving Students and Identified Gifted Students

Abstract: High achieving students or “bright children” are often denied access to gifted services because they do not meet “gifted” criteria. Although psychosocial factors play an integral role in academic success, and can be useful in providing a clearer picture of student need, they are seldom considered in the decision to identify a student for gifted services. This study compared identified gifted students and non-identified high achieving students on their self-perceptions of several psychosocial factors to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
11
0
6
Order By: Relevance
“…Identification appears to increase academic self-perception for many of these underachievers which supports Ritchotte et al (2016). Students were empowered by the student agency involved in the use of Maker Model strategies.…”
Section: Conclusion and Recommendationsmentioning
confidence: 71%
“…Identification appears to increase academic self-perception for many of these underachievers which supports Ritchotte et al (2016). Students were empowered by the student agency involved in the use of Maker Model strategies.…”
Section: Conclusion and Recommendationsmentioning
confidence: 71%
“…Perhaps the most frequently cited individual-level factor in the literature linked to the development of gifted potential is the student’s motivation to achieve (Abu-Hamour & Al-Hmouz, 2013; McCoach & Siegle, 2003; Ritchotte, Suhr, Alfurayh, & Graefe, 2016; Wellisch & Brown, 2013). Defined as “the processes that allow people to select appropriate goals and to pursue them successfully” (Lin-Siegler, Dweck, & Cohen, 2016), motivation has long been referenced by theorists in the field as a key element of giftedness (Csikszentmihalyi, Rathunde, & Whalen, 1997; Gagné, 2000; Sternberg, 2001).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…32 Previous research has found that through proper stage attainment individuals gain emotional, social and mental well-being. [22][23][24][25][26][27][28]31,[33][34][35] Stages are either attained or unsuccessful through the dynamic push and pull of interpersonal relationships and psychological developments, hence the term "psychosocial development". 32 Caregivers must consistently meet physiological needs such as feeding and changing early in development and then encourage autonomous actions such as walking, changing, and toileting.…”
Section: Development As a Protective Factormentioning
confidence: 99%
“…32 Successful relationships have been shown to improve and even predict academic performance. [22][23][24][25][26][27][28]31,[33][34][35] Researchers have also found that development of certain psychosocial characteristics have a major impact on academic performance. Many researchers found motivation plays a vital role in academic performance.…”
Section: Development As a Protective Factormentioning
confidence: 99%